Strategies for Increasing Investment through Analysis of Leading Sectors in Pohuwato Regency: an Analysis of Location Quotient and Shift Share - KURNIA, LUSI (Universitas Gorontalo, 2026)
Pohuwato Regency in Gorontalo Province possesses significant economic potential but faces challenges in transforming its economy from extractive sectors. This study aims to formulate strategic recommendations for the Pohuwato Regency Government to enhance investment in leading sectors to drive regional economic growth. The research method employs both quantitative and qualitative approaches using Location Quotient (LQ), Shift-Share Analysis (SSA), and Klassen Typology to map the regional economic structure. Additionally, Focus Group Discussions (FGD) were utilized to shape investment policy directions. Data collection was conducted through the compilation of secondary data for the 2020-2024 period. The study results identify Agriculture, Forestry, and Fisheries and Manufacturing Industries as basic and prime sectors requiring investment priority. Recommended policy strategies include: (1) creating a competitive national business climate; (2) focusing investment on basic needs, priority industries, export orientation, green investment, infrastructure, and innovation; (3) protecting and developing MSMEs and cooperatives; (4) improving local workforce quality; (5) providing investment facilities; (6) improving investment distribution; (7) promoting investment; and (8) fostering investment cooperation. Implementation of these strategies is expected to create a competitive and sustainable business climate in Pohuwato Regency